SAT0323 The endothelial-to-mesenchymal transition (ENDOMT) in scleroderma can be prevented by the use of dual endothelin receptor antagonists bosentan and macitentan. (15th June 2017) - Corallo, C; Cutolo, M; Soldano, S; Montella, A; Chirico, C; Nuti, R; Giordano, N
Abstract : Background: Systemic sclerosis (SSc) is characterized by early vascular abnormalities and subsequent fibroblast activation and differentiation into myofibroblasts, leading to fibrosis. Recently, endothelial-to-mesenchymal transition (EndoMT), a complex biological process in which endothelial cells lose their specific markers and acquire a mesenchymal or myofibroblastic phenotype, has been reported in SSc. Objectives: The goal of the study was to evaluate the potential of endothelin-1 (ET-1) dual receptor antagonists bosentan (BOS) and macitentan (MAC) to antagonize EndoMT in vitro . Methods: 20 patients with limited SSc were enrolled and underwent double skin biopsy (affected and nonaffected skin). Fibroblasts and microvascular endothelial cells (MVECs) were isolated from biopsies. Mono- or coculture of MVECs (isolated from nonaffected skin) with fibroblasts (isolated from affected skin and stimulated with ET-1 and transforming growth factor beta [TGF-β]) were performed. In cocultures, the MVEC layer was left undisturbed or was preincubated with either BOS or MAC. After 48 h of coculture, MVECs were analyzed for their capillary formation ability and for messenger RNA and protein expression of different vascular (CD31, vascular endothelial growth factor-A [VEGF-A], VEGF-A165b) and profibrotic (alpha-smooth muscle actin [α-SMA], collagen type I [Col I], TGF-β) molecules. Results: MVECs showed a reduced capillary formation ability when cocultured with SSc fibroblasts with respect to mono cultures. CD31 and VEGF-A resulted in downregulation, while VEGF-A165b, the antiangiogenic isoform, resulted in upregulation. At the same time, mesenchymal markers α-SMA, Col I, and TGF-β resulted in overexpression in MVECs. Capillary formation ability was restored when MVECs were preincubated with BOS or MAC, also reducing the expression of mesenchymal markers and restoring CD31 expression as well as the imbalance between VEGF-A and VEGF-A165b. Conclusions: BOS and MAC seem able to antagonize EndoMT phenomenon in MVECs in vitro . Blocking EndoMT is important for two reasons: first, because capillary formation ability in MVECs can be restored; second, because the endothelium-derived fibrotic development in SSc can be counteracted. Acknowledgements: Thanks to Prof. Bashar Kahaleh and to Dr. Yongqing Wang from University of Toledo Medical Center, Division of Rheumatology and Immunology, OH, USA, for providing SSc microvascular endothelial cells. Disclosure of Interest: None declared